Improving Students’ Ability in Writing Scientific Papers Through Process Approach - Fitri Ayu; Devi Anggriani; Nizamuddin (International Forum of Researchers and Lecturers, 2023)
One of the writing skills that must be mastered by intellectuals is writing scientific papers. The Indonesian curriculum covers all language skills, including writing. The curriculum is described in the Competency Standards and Basic Competencies (SK and KD) from elementary to high school levels. This study aims to determine the ability of students in class XII MIA 4 SMA Panca Budi in writing scientific papers that will be useful for continuing their education to the university level. This research was conducted as a solution offer that would guide these students to write using an approach, namely